Detection of intramyocardially injected DiR-labeled mesenchymal stem cells by optical and optoacoustic tomography - Berninger, Markus T.; Mohajerani, Pouyan; Wildgruber, Moritz; Beziere, Nicolas; Kimm, Melanie A.; Ma, Xiaopeng; Haller, Bernhard; Fleming, Megan J.; Vogt, Stephan; Anton, Martina; Imhoff, Andreas B.; Ntziachristos, Vasilis; et al. (Photoacoustics, 2017)
The distribution of intramyocardially injected rabbit MSCs, labeled with the near-infrared dye 1,1′-dioctadecyl-3,3,3′,3′-tetramethylindotricarbo-cyanine-iodide (DiR) using hybrid Fluorescence Molecular Tomography-X-ray Computed Tomography (FMT-XCT) and Multispectral Optoacoustic Tomography (MSOT) imaging technologies, was investigated. Viability and induction of apoptosis of DiR labeled MSCs were assessed by XTT- and Caspase-3/-7-testing in vitro. 2 × 106, 2 × 105 and 2 × 104 MSCs labeled with 5 and 10 μg DiR/ml were injected into fresh frozen rabbit hearts. FMT-XCT, MSOT and fluorescence cryosection imaging were performed. Concentrations up to 10 μg DiR/ml did not cause apoptosis in vitro (p > 0.05). FMT and MSOT imaging of labeled MSCs led to a strong signal. The imaging modalities highlighted a difference in cell distribution and concentration correlated to the number of injected cells. Ex-vivo cryosectioning confirmed the molecular fluorescence signal. FMT and MSOT are sensitive imaging techniques offering high-anatomic resolution in terms of detection and distribution of intramyocardially injected stem cells in a rabbit model.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cell labeling; Fluorescence molecular imaging; Intramyocardial injection; Mesenchymal stem cells; Multispectral optoacoustic tomography; Rabbit heart